Josie and Henry Simon talk about local legends, the supernatural, and storytelling - Thomas, Gerald (1972)
Henry et Josie Simon parlent d'un trésor enfoui, des superstitions autour de l'argent, et des pirates. Ils racontent quelques contes, des histoires de fantômes, et des histoires à dormir debout. Il y a de la conversation générale à propos des contes. -- Henry and Josie Simon talk about a buried treasure, superstitions about money, and pirates. They tell a few tales, a ghost tale, and a couple of tall tales. There is some general conversation about stories and storytelling. Transcription du F1685/C2315/CD-F2103 -- Transcript of F1685/C2315/CD-F2103